Determination of the Ex Vivo Rates of Human Immunodeficiency Virus Type 1 Reverse Transcription by Using Novel Strand-Specific Amplification Analysis - Thomas, David C. (American Society for Microbiology, 2007)
Replication of human immunodeficiency virus type 1 (HIV-1), like all organisms, involves synthesis of a minus-strand and a plus-strand of nucleic acid. Currently available PCR methods cannot distinguish between the two strands of nucleic acids. To carry out detailed analysis of HIV-1 reverse transcription from infected cells, we have developed a novel strand-specific amplification (SSA) assay using single-stranded padlock probes that are specifically hybridized to a target strand, ligated, and quantified for sensitive analysis of the kinetics of HIV-1 reverse transcription in cells. Using SSA, we have determined for the first time the ex vivo rates of HIV-1 minus-strand DNA synthesis in 293T and human primary CD4(+) T cells (∼68 to 70 nucleotides/min). We also determined the rates of minus-strand DNA transfer (∼4 min), plus-strand DNA transfer (∼26 min), and initiation of plus-strand DNA synthesis (∼9 min) in 293T cells. Additionally, our results indicate that plus-strand DNA synthesis is initiated at multiple sites and that several reverse transcriptase inhibitors influence the kinetics of minus-strand DNA synthesis differently, providing insights into their mechanism of inhibition. The SSA technology provides a novel approach to analyzing DNA replication processes and should facilitate the development of new antiretroviral drugs that target specific steps in HIV-1 reverse transcription.